Attainment of gross motor milestones in children with Down syndrome in Kosovo - developmental perspective - Samire Beqaj; Njomza Jusaj; Vujica Živković (Medicinski glasnik, 2017)
Aim: To investigate the age (in months) at which motor skills are developed in children with Down syndrome (DS), and compare it to the age of the development of the same skills in both, children with typical development (TD), and children with DS reported by four other studies. Methods: Sixteen children (7 girls and 9 boys) were monthly assessed for the development of nineteen motor skills between 2008 and 2011. The mean ages when the skills were accomplished were presented using descriptive statistics. Independent T-samples test (significance < 0.05) was used to compare the mean developmental ages from our study with those seen in children with TD (Comparison 1) and also in children with DS reported by four other authors (Comparison 2a-2d). Results: Children with DS developed at a significantly slower pace compared to children with TD (p=0.005). Generally, delay and variance of developmental age in children with DS increased chronologically with the complexity of the skills. No significant difference was found between developmental age in children from the present study and children with DS from other studies. Conclusion: The rate of attainment of motor skills is delayed in children with DS in comparison to children with TD, however, the developmental sequence is the same. The delayed development is more prominent in more complex skills.
Keywords: motor skills; physical therapy; early intervention